THE RELATIONSHIP BETWEEN INVESTMENT AND EXPORT OF LIVESTOCK SECTOR TO ECONOMIC GROWTH IN INDONESIA - Suhartina, Suhartina (Pattimura Proceeding, 2023)
Introduction/Main objectives: This study aims to analyze the relationship between investment and exports of the livestock sector on economic growth in Indonesia. The livestock sector performs a crucial position for Indonesia's monetary growth because it's miles one of the sectors that contributes to the national economy. Background Problems: Based on this, the authors are interested in knowing how the relationship between investment and exports of the livestock sector to economic growth in Indonesia. Novelty: This research is a topic that has not been widely studied in Indonesia, the field of economics with the topic of economic growth, investment and exports has been studied very much, but those who see the relationship between investment and exports of the livestock sector on Indonesia's economic growth are still few. Therefore, linking livestock sector investment and exports to Indonesia's economic growth is the novelty of this study. Research methods: This research uses Ordinary Least Square analysis technique. The type of data used is secondary data in the form of annual quantitative figures from 2016-2020 obtained from the Central Statistics Agency. Results: The results showed that livestock sector investment had a positive and insignificant effect on economic growth. On the other hand, exports of the livestock sector (livestock, livestock products, non-food animal products and veterinary drugs) have a negative and insignificant effect on economic growth. Conclusion: The conclusion of the study is that livestock sector investment affects economic growth while livestock sector exports have no effect. These results reveal that to increase economic growth, it is necessary to improve Indonesia's export performance by doing numerous ways, one in all that's via enhancing the export management machine, growing research and improvement of Indonesian merchandise, enhancing infrastructure facilities and infrastructure, change rate stability and expanding non-conventional markets so that provide added value for exports which in turn can increase Indonesia's economic growth